No More Lemmings, Please – Reflections on the Communal Authority Thesis - Hussain, Waheed (Journal of business ethics, 2009)
A key feature of ISCT is the claim that individuals are required to comply with the norms that are “accepted by a clear majority of the community as standing for an ethical principle” [Donaldson and Dunfee, 1999, The Ties that Bind (Harvard Business School Press, Boson, MA), p. 39], so long as these norms are consistent with hypernorms. I refer to this as the communal authority thesis. Many people see the communal authority thesis as an attractive feature of ISCT, a welcome move away from the abstraction of principle-based ethical theories. I argue in this article, however, that the communal authority thesis is false: we do not have a general moral obligation to comply with the accepted norms in our community. I consider and reject several defenses of the communal authority thesis, including the central arguments put forward by Donaldson and Dunfee. I go on to develop my own position, which accepts that social norms can be important from the moral point of view. However, I argue that social norms are important because they can shape the morally important features of our situation, not because we have a general obligation to comply with these norms as such. I use examples such as gift giving in Japan and the housing crisis to illustrate my position.